Analisis Studi Kelayakan Bisnis terhadap Usaha Kerupuk Sari Rasa di Desa Deli Serdang Ditinjau Dari Aspek Produksi, Aspek Pemasaran dan Aspek Keuangan - Dara Puspita; Nadya Ervina; Habib Matwar (VISA: Journal of Vision and Ideas, 2022)
This study aims to determine the feasibility of the business of flavored crackers to entermine the feasibility of the non-financial aspects and the feasibility of the financial aspects. Feasibility analysis uses analysis of non-financial aspects, namely aspects of productions and marketing aspects. Meanwhile, the analytical tool used for the financial aspect is Payback Period (PP) , Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI) analysis to determine whether a business is feasible or not. The results showed that the flavored cracker business and business production aspects were deemed feasible,because the business location was strategic and easily accessible to consumers, the technology used was alsomodern,the production process also easy. Aspects of proper marketing, with high quality products due to imported raw materials, the price is also affordable. So that all people can buy it, the distribution is also quite wide, and the promotion given by the owner also makes consumers aware of the products they sell. Keywords: Business feasibility studies, production aspects, marketing aspects, legal aspects.